Differences between older and younger Poles in functional food consumption, awareness of metabolic syndrome risk and perceived barriers to health improvement - Wadolowska, Lidia (2009)
The aim of the study was to analyze the differences between older and younger Poles in functional food consumption, awareness of metabolic syndrome risk and perceived barriers to health improvement. A national representative sample of 1005 adults aged 15+ was selected for the study. The eldest age group (65+ years) more often than the youngest age group (15-24 years) reported having high blood cholesterol (OR = 12.30), high blood pressure (OR = 10.61), central obesity (OR = 7.94), high blood sugar (OR = 4.33), high stress level (OR = 2.12). A smaller number of the older in comparison to the younger consumed probiotic yoghurt drinks (OR = 0.48), foods with added vitamins and/or minerals (OR = 0.31), energy drinks (OR = 0.05) at least once a week. Younger people were more likely to report that they were ready to increase physical activity (OR = 0.21), cut down on or stop smoking (OR = 0.48) or drink less alcohol (OR = 0.46), but more of them would prefer to take medicines than food-related intervention (OR = 3.05). Older people rarely complained about a lack of time (OR = 0.26) to improve their health. In conclusion, intervention to promote a healthy lifestyle to prevent and treat metabolic syndrome would need to target older Poles.